PENGEMBANGAN BAHAN AJAR BERBASIS MICROSITE PADA MATERI PANCASILA DALAM KEHIDUPANKU KELAS V SEKOLAH DASAR - Yunita Nur Shavirah; Oktaviani Adhi Suciptaningsih; Riska Pristiani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to create microsite-based learning materials of Pancasila in My Life for grade V elementary school students. The development model applied is ADDIE (Analysis, Design, Development, Implementation, and Evaluation). The product is designed in a microsite-based cloud learning format including learning modules, teaching materials, literacy, LKPD, and evaluation. Validation by media and material experts shows that the product is very suitable for use, with a percentage of 86.1% each. Experiments on teachers and students showed excellent results with eligibility scores of 87.5% and 97.72%, respectively. These findings indicate that microsite-based learning materials are effective in supporting thematic learning and increasing students' interest in learning. This study offers innovative solutions in the creation of learning media that are in line with the Independent Curriculum and the demands of learning in the 21st Century.